Evaluating the Cytotoxic Effects of Ethanol and n-Hexane Extracts from Black Cumin Seeds (Nigella sativa) on B16F10 Mouse Melanoma Cells : A Preliminary Investigation into Vitiligo Treatment - Pratiwi, Dian; Mariya, Silmi; Rayendra, Raendi; Setiyono, Agus (HAYATI Journal of Biosciences, 2025)
Black cumin (Nigella sativa) is a herbal plant that has been cultivated locally in Indonesia and is traditionally used for various diseases. Thymoquinone, one of the main components, is rich in biological activity. In several countries, topical application of its oil on human skin with vitiligo can stimulate skin repigmentation with minimal side effects. This study aims to determine the viability of B16F10 melanoma mouse cells against ethanol and n-hexane extracts of black cumin seeds through the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. The ethanol extract (EE) yield was 14.306%, and the n-hexane extract (NHE) was 7.442%. Phytochemical screening of EE detected flavonoids, alkaloids, saponins, and steroids, and High-performance liquid chromatography (HPLC) detected 0.040% thymoquinone. The MTT test showed cell viability was >100% from EE at all treatment concentrations, namely 0.75-100 ppm and only 0.75-6.25 ppm for NHE. In conclusion, this study indicates that 96% EE of Nigella sativa is less toxic than NHE on B16F10 mouse melanoma cells and has potential as an alternative treatment for vitiligo, which needs to be proven in further research.